Formation and maintenance of morphogen gradients: An essential role for the endomembrane system in Drosophila melanogaster wing development. - Erickson, J.L. (Fly, 2011)
As early as 1964 it was suggested that simple diffusion of morphogens away from their secretion source did not provide an adequate explanation for the formation and maintenance of morphogen gradients. Involvement of the endosome in morphogen distribution models provides an explanation for the slow, directional movement of morphogens, as well as their ability to form intracellular and extracellular gradients independent of morphogen production rates. Drosophila melanogaster morphogens Wg and Dpp form stable, steep, long-range gradients that specify the polarity of the wing disc. The process of endocytosis is imperative to the two central themes in gradient formation: active transport facilitating long-range signaling and degradation of morphogen to sustain gradient shape. This review investigates the endomembrane-mediated processes of re-secretion, degradation and argosome transport of Wg and Dpp in the hope that a better understanding of the endomembrane system will contribute to a more accurate and comprehensive model for morphogen gradient formation and maintenance.